Suprastruktur dan Infrastruktur Politik dalam Kehidupan Demokrasi - Muklis Siregar; Elly Warnisyah Harahap (UNES Law Review, 2024)
This article focuses on studying and analyzing in depth the mechanisms of the political system in the superstructure and infrastructure. The political system is defined as a collection or total of various activities in the country related to the public interest, including the process of determining goals, efforts to realize goals, making decisions, and preparing priority scales. . Political structure, as a result of these subsystems, can be divided into political infrastructure and political superstructure. Political infrastructure involves the basic elements that support the functioning of the political system, while political superstructure includes more complex elements and is related to providing authority and control. In this context, mechanisms are important to maintain the balance and functioning of a political system. Each political structure needs to interact with other political structures, based on the special functions that each structure has. In a country's political system, there are 2 (two) main components that run the wheels of government, namely political superstructure and political infrastructure. The political superstructure is the institutions mentioned in a country's constitution and which carry out executive, legislative and judicial functions and are tasked with making policies related to the public interest. Meanwhile, political infrastructure is a group of political forces in society that actively participates in influencing government policy as a form of democracy. If classified, there are 4 (four) forces, namely: Political Parties, Interest Groups, Pressure Groups. , Political communication media.